Ellagic acid prevents cisplatin-induced oxidative stress in liver and heart tissue of rats - Yuece, Abdurrauf; Atessahin, Ahmet; Ceribasi, Ali Osman; Aksakal, Mesut (Wiley, 2007)
Cisplatin is one of the most active cytotoxic agents in the treatment of cancer. High doses of cisplatin have also been known to produce hepatotoxicity, and several studies suggest that supplemental antioxidants can reduce cisplatin-induced hepatotoxicity. The present study was designed to determine the effects on the liver and heart oxidant/antioxidant system and the possible protective effects of ellagic acid on liver and heart toxicity induced by cisplatin. The control group received 0.9% saline; animals in the ellagic acid group received only ellagic acid (10 mg/kg); animals in the cisplatin group received only cisplatin (7 mg/kg); animals in cisplatin + ellagic acid group received ellagic acid for 10 days after cisplatin. The rats were killed at the end of the treatment period. Malondialdehyde (MDA) and glutathione (GSH) levels, glutathione-peroxidase (GSH-Px) and catalase (CAT) activities were determined in liver and heart tissue. While administration of cisplatin increased the MDA levels in liver and heart tissues, it decreased the GSH, GSH-Px and CAT in these samples when compared to the control group. The administration of ellagic acid to cisplatin-treated rats decreased the MDA levels, and increased GSH, GSH-Px and CAT in these samples. Cisplatin caused marked damages in the histopathological status of liver and heart tissues. These damages were ameliorated by ellagic acid administration. In conclusion, ellagic acid may be used in combination with cisplatin in chemotherapy to improve cisplatin-induced oxidative stress parameters.
Keywords: Vitamin-E Succinate; Induced Nephrotoxicity; Lipid-Peroxidation; Induced Toxicity; Antioxidants; Selenium; Chemotherapy; Damage; Supplementation; Mutagenicity